2015
DOI: 10.2971/jeos.2015.15016
|View full text |Cite
|
Sign up to set email alerts
|

UV distributed Bragg reflectors build from porous silicon multilayers

Abstract: UV Distributed Bragg reflectors were fabricated by a two-step thermal oxidation process over porous silicon multilayers (PS-ML), which were prepared by room-temperature electrochemical anodization of silicon wafers. The optical behavior of the PS-ML before and after oxidation was studied by reflectance measurements. It was observed an UV shift from 430 to 300 nm in the peak of the reflectance spectrum after oxidation of the PS-ML. This was attributed to the presence of silicon oxide over the surface of the sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Other authors reported a mixture of OPS and titanium dioxide (TiO 2 ) to form transparent BRs in the VIS range where the oxidation process eliminates optical losses across the VIS range 23 . Several studies on BRs have been made in the UV range using different Si substrates and applying two oxidation processes [20][21][22] . The oxidation was used for stabilization of the refractive index; the authors did not compare between experimental and theoretical results, they only supported their results with the experimental reflection spectrum confirming a decrease of light absorption, and by keeping the same amplitude reflection level in the VIS and UV range.…”
Section: Porous Silicon Microcavities On Silicon Substrates and Quartmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors reported a mixture of OPS and titanium dioxide (TiO 2 ) to form transparent BRs in the VIS range where the oxidation process eliminates optical losses across the VIS range 23 . Several studies on BRs have been made in the UV range using different Si substrates and applying two oxidation processes [20][21][22] . The oxidation was used for stabilization of the refractive index; the authors did not compare between experimental and theoretical results, they only supported their results with the experimental reflection spectrum confirming a decrease of light absorption, and by keeping the same amplitude reflection level in the VIS and UV range.…”
Section: Porous Silicon Microcavities On Silicon Substrates and Quartmentioning
confidence: 99%
“…F. Morales has manufactured BRs at room temperature. To stabilize the optical parameters of BRs in the UV range dry oxidation is performed 22 . BRs based on Oxidized Porous Silicon (OPS) and TiO 2 were manufactured by Christian R. Ocier.…”
mentioning
confidence: 99%
“…Optical losses in the VIS and UV range due to light absorption are found frequently in PS. This absorption loss impedes the fabrication of PS filters in the UV range, but these losses can be decreased if the PS structure is thermally oxidized in an oxygen environment [35,36]. Figure 6 (MF1) shows the theoretical (a) and experimental (b) absorbance spectrum of five microcavities.…”
Section: Optical Losses Due To Light Absorptionmentioning
confidence: 99%
“…However, many drawbacks have been found in these filters, such as high chemical instability, high photon losses due to light absorption, and scattering in the visible and UV ranges. Some solutions to these problems have been identified by carrying out dry oxidation in PS structures [32,34], and recently it has been possible to manufacture porous Si-SiO 2 filters (BRF and MF) in the UV range [34][35][36]. Our specific goal is integrating a PS MF in a photodetector to enlarge the responsivity spectrum bandwidth.…”
mentioning
confidence: 99%
“…This modulation is achieved by the application of different current pulses. This technique allows for us to design multilayer structures that are based on porous silicon, like distributed Bragg reflectors (DBRs) [ 1 , 2 , 3 ], rugate filters [ 3 , 4 ], and microcavities (MC) [ 5 , 6 , 7 ]. Furthermore, due to the high internal surface area of Psi, all of the devices mentioned above are good candidates for sensing biological and chemical substances [ 8 , 9 , 10 ] and gas [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%